The Status of Teacher Introduction in Catholic Schools: Perspectives From the United States and Canada - Brock, Barbara L.; Chatlain, Greg (Catholic Education: A Journal of Inquiry and Practice, 2008)
Catholic schools struggle with issues of teacher recruitment and retention. The experience of new teachers-both those recently graduated from college as well as those new to the Catholic sector-often impacts retention rates. This article presents a study of induction programs for such new teachers in the US and Canada, summarizes current trends, and offers recommendations for the future.